STUDI EKSPERIMENTAL BALOK PROFIL KANAL (C) FERROFOAM CONCRETE DENGAN PENAMBAHAN POZZOLAN (STUDI KASUS BEDA TINGGI 300 MM, 450 MM DAN 600 MM) - Ismatullah, Aulia; Afifuddin, Mochammad; Aulia, Teuku Budi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract: Deck girder construction is one of the most important elements in the constructions of bridges. In general, the girder is made of steel, wood, or concrete. However, the use of these materials has their own limits. These problems led to the idea to study and make profiles ferro foam concrete canal with the addition of pozzolan as an alternative material that can be used in the construction of the bridge girder. This research was conducted to obtain information on the effect of the addition of natural pozzolan materials to the variation in height (h) in the structure of beam canal profile ferro foam concrete with the configuration I in accepting the loads that work. Specimens used in this study was 16 Specimens Profile Canal C are assembled into 8 profiles I with height variations (h), wingspan (bf) on the canal profile is 300 mm, 150 mm and 450 mm; 225 mm, 600 mm and 300 mm and thickness (tw = tf) on the canal profile that is 30 mm, 40 mm, 50 mm. the average of concrete compressive strength (f'c) 32,56 MPa and Specific Gravity (SG) 1,6 and Cement water factor (FAS) 0,4 with additional 10% in Pozzolan, yield stress reinforcement D8 421 MPa, and yield stress wiremesh 530 MPa. This research results obtained are capable of maximum load carried by the canal profile (C) which is configured I with a height of 300 mm is (PCBP 300.150.50) able to withstand the maximum load by 20,41 tons with a deflection of 24,43 mm, to the high-profile 450 mm is equal to 33,00 tons with the deflection of 24,43 mm, namely the test specimen PCBP 450.225.50 and for the profile height of 600 mm is able to accept 39,93 tons with a deflection of 28,55 mm, namely in the test specimen PCBP 600.300.50. The results obtained can be applied in the construction of short span bridges (less than 40 m). Increasing of ultimate load which are capable carried by the canal profile (C) with 600 mm height is 1,95 times of the profile with a height of 300 mm. the capable of the 450 mm height of the profile is 1,65 times with the height of profile is 300mm. the research result showed that with the addition of the height of the profile, the profile capacity is increased.Abstrak: Konstruksi gelagar jembatan merupakan salah satu elemen terpenting dalam pembangunan jembatan. Pada umumnya gelagar tersebut terbuat dari baja, kayu, ataupun beton. Namun, penggunaan material tersebut memiliki keterbatasan masing-masing. Permasalahan ini memunculkan suatu ide untuk meneliti dan menjadikan profil kanal ferro foam concrete sebagai alternatif material yang dapat digunakan pada konstruksi gelagar jembatan. Penelitian ini dilakukan dengan tujuan untuk mendapatkan informasi tentang perilaku profil kanal (C) ferro foam concrete terhadap studi kasus variasi beda tinggi (h) dengan penambahan pozzolan alami dalam menerima beban-beban yang bekerja. Benda uji yang digunakan dalam penelitian ini adalah 16 benda uji Profil Kanal C yang dirangkai menjadi 8 profil I dengan variasi beda tinggi (h), lebar sayap (bf) pada profil kanal yaitu 300 mm; 150 mm, 450 mm; 225 mm, 600 mm; 300 mm dengan tebal (tw=tf) keseluruhan profil yaitu 30 mm, 40 mm, 50 mm. Hasil kuat tekan beton rata-rata (fc) adalah 32,56 MPa dengan Specifik Gravity (SG) 1,6 dan Faktor Air Semen (FAS) 0,4 dan penambahan pozzolan sebesar 10% dan tegangan leleh tulangan D8 421 MPa, dan tegangan leleh wiremesh 530 MPa. Hasil penelitian yang didapat yaitu beban maksimum yang mampu dipikul oleh profil kanal (C) yang dikonfigurasikan I dengan tinggi 300 mm adalah (PCBP 300.150.50) mampu menahan beban maksimum sebesar 20,41 Ton dengan lendutan sebesar 24,43 mm, untuk profil dengan tinggi 450 mm adalah (PCBP 450.225.50) mampu menahan beban maksimum sebesar 33 Ton dengan lendutan sebesar 31,25 mm dan untuk profil dengan tinggi 600 mm adalah (PCBP 600.300.50) mampu menahan beban maksimum sebesar 39,93 Ton dengan lendutan sebesar 28,55 mm. Pertambahan beban ultimit yang mampu dipikul oleh profil canal (C) dengan tinggi 600 mm adalah sebesar 1,95 kali dari profil dengan tinggi 300 mm dan untuk profil dengan tinggi 450 mm mampu menahan beban sebesar 1,62 kali dari profil dengan tinggi 300 mm. Hasil pengujian menunjukkan dengan adanya penambahan tinggi profil maka kapasitas dari profil tersebut menjadi meningkat.